(untitled) (Agricultural Engineering, 2016)
This work is a continuation of research on the differences in the sublimation speed of free ice and ice contained in the porous material. The results of previous research were published in Technica Agraria 12(1-2)/2013 (Diakun, Dolik, Kopec “The sublimation speed of free ice and ice in the sprat carcass”). A test stand used in studies was supplemented by a cold trap to prevent the steam flow into the vacuum pump and for the intensification of the ice sublimation process. The comparative tests: with the cold trap and without were performed. The research material (samples) was in the form of ice nugget, frozen sprat carcasses and ice frozen within the sponge (porous material model). The aim of the study was to examine the cold trap impact on the conditions within the vacuum chamber during sublimation and the speed of the process. The differences in the sublimation speed for the free ice, the ice from the frozen sprat and from the model were rated. The results showed a significant increase in the sublimation speed during the process with the active cold trap.